2022
DOI: 10.3390/ani12070914
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Hematological and Biochemical Profiles in Ovariohysterectomized Bitches Using an Alfaxalone–Midazolam–Morphine–Sevoflurane Protocol

Abstract: The aim of this study was to monitor hematochemical changes during and after OHE in bitches. Twenty-four females were anesthetized with alfaxalone, midazolam, morphine and sevoflurane. Blood samples were taken before anesthesia (T0), at 30 (T1), and 60 min (T2), at 3 (T3), 6 (T4), 12 (T5), and 24 h (T6), and at 3 (T7) and 7 days (T8) from the start of surgery. Red blood cells (RBC) and packed cell volume (PCV) decreased significantly from T1 to T5 and hemoglobin (HB) concentration from T4 to T6. Both the white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…As for the blood count parameters such as PCV, HB and PLT, there was a significant decrease after surgery in both groups, probably due to perioperative fluid administration, splenic sequestration, and surgical trauma. These results were in line with those published recently by Rubio et al [ 60 ], where significantly decreased values were also determined in PCV and PLT compared to baseline after open OHE in healthy dogs. Additionally, some authors observed greater loss of blood in the laparotomy with respect to laparoscopic techniques [ 10 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As for the blood count parameters such as PCV, HB and PLT, there was a significant decrease after surgery in both groups, probably due to perioperative fluid administration, splenic sequestration, and surgical trauma. These results were in line with those published recently by Rubio et al [ 60 ], where significantly decreased values were also determined in PCV and PLT compared to baseline after open OHE in healthy dogs. Additionally, some authors observed greater loss of blood in the laparotomy with respect to laparoscopic techniques [ 10 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, similar to the results of our study, they did not find any differences in the complete blood count parameters between both groups. As for the concentration of WBC, previous publications have reported significantly increased post-operative values after OHE [ 42 , 60 ]. However, in our study, both groups showed a significant decrease in the immediately postoperative period, probably due to hemodilution.…”
Section: Discussionmentioning
confidence: 99%
“…With the return of vital values to normal levels in the following h the effect of the anesthetics was seen to have disappeared. Numerous studies that have used various surgical procedures and anesthesia regimens to assess the alterations in hematochemical parameters in OHE bitches have reported varying results [16]. Intraoperative blood loss of less than 15% of blood volume is not anticipated to result in clinical symptoms in non-anemic human patients, although the loss of less than 30% of intraoperative blood volume has been proposed as a red cell transfusion trigger in otherwise healthy people [17].…”
Section: Resultsmentioning
confidence: 99%
“…Neutrophils showed an increase at 60 minutes followed by reduction at 6 hours and reached baseline value by 24 hours. Neutrophilia could be attributed to the stress caused by anaesthetic drugs, surgical trauma and activation of the adrenal cortex (Rubio et al, 2022). All these changes in the haematological parameters were within the normal physiologic range.…”
Section: Discussionmentioning
confidence: 96%
“…The decrease in total proteins could be due to hemodilution or secondary elevation of globulins (Dewangan et al, 2016). Surgical and anaesthetic stress leads to the altered endocrine secretion of the insulin antagonisms like growth hormone (Rubio et al, 2022). Increase in BUN levels might be due to temporary inhibitory effect of drugs on renal blood flow resulting in consequent reduction in glomerular blood flow (Dewangan et al, 2016).…”
Section: Haemato-biochemical Parametersmentioning
confidence: 99%